PELATIHAN TENTANG LONTAR PRAKEMPA DAN MAKNA SEMBAHYANG HINDU PADA PENGURUS SEKEHA GONG MAHA WIDYA MERDANGGA UNHI DENPASAR - I MADE RUDITA; I WAYAN SUKADANA (UNHI Press, 2020)
The community service activities were carried out at the Indonesian Hindu University on Jalan Sangga Langit Tembawu, East Denpasar District, Denpasar City, especially at the Sekeha Gong Management Maha Widya Merdangga. This Sekeha Gong administrator will be a model for all Sekeha Gong members regarding understanding of the contents of the Lontar Prakempa and the meaning of Hindu prayer. The problem that is currently happening to the Sekeha Gong Management is the lack of understanding of the Sekeha Gong Management regarding the contents of the Lontar Prakempa and the meaning of Hindu prayer. The impact that can be caused by the inability of the Sekeha Gong Management to explain the contents of the Lontar Prakempa and the meaning of this Hindu prayer is the emergence of dissatisfaction from the members of Sekeha Gong Maha Widya Merdangga in general and they did not make this Sekeha Gong Management a model to emulate. This community service activity was carried out in an effort to help this Sekeha Gong Management to understand the contents of the ejection of the Prakempa and the meaning of this Hindu prayer. This can be achieved by conducting training on the contents of the palm leaf and the meaning of this Hindu prayer. This activity is expected to produce output so that the Sekeha Gong Maha Widya Merdangga Board is 100% able to explain the contents of the ejection of the Prakempa and the meaning of this Hindu prayer so that the satisfaction of Sekeha Gong members increases.